2021
DOI: 10.1029/2021gl094657
|View full text |Cite
|
Sign up to set email alerts
|

Global Frequency and Geographical Distribution of Nighttime Streamer Corona Discharges (BLUEs) in Thunderclouds

Abstract: gests streamer coronas to be the cause of narrow bipolar events (NBEs). NBEs were originally detected by Le Vine (1980) in the form of strong radio frequency sources from in-cloud electrical activity. Such sources were characterized by short-duration (10-30  E s) bipolar sferic waveforms recorded in the very low frequency (VLF)/low frequency (LF) (10-400 kHz) range (Smith et al., 1999). NBEs can also appear accompanied by strong very high frequency (VHF) (30-300 MHz) radiation bursts. N EFirst Negative System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 67 publications
7
48
0
Order By: Relevance
“…A total of 57,636 blue discharge candidates were detected, consistent with numbers quoted in (Soler et al., 2021). However, because our analysis require availability of ERA5, GLD360, satellite data and that the event able to be geolocated, only 11,625 events are included in our blue discharge data set.…”
Section: The Observationssupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 57,636 blue discharge candidates were detected, consistent with numbers quoted in (Soler et al., 2021). However, because our analysis require availability of ERA5, GLD360, satellite data and that the event able to be geolocated, only 11,625 events are included in our blue discharge data set.…”
Section: The Observationssupporting
confidence: 87%
“…Flashes of light from thunderstorm clouds have been observed in the second positive band of Nitrogen (N 2 2P) at 337 nm (blue) with no emission in the main lightning leader lines of OI at 777.4 nm (red), suggesting they are made of streamer breakdown. They are observed in the upper regions of clouds, with some at the very top (Chang et al., 2010; Chanrion et al., 2017; Dimitriadou et al., 2022; Kuo et al., 2009; Krehbiel et al., 2008; Lyons et al., 2003; Liu et al., 2015; Soler et al., 2021), and have been shown to be associated with Narrow Bipolar Events (NBEs) observed in VLF/LF radio signals (3–300 kHz) (Li et al., 2021; Liu et al., 2018; Soler et al., 2020). They are related to a wider family of discharges, which includes blue starters and blue jets that propagate from the cloud tops into the stratosphere, or beyond to the ionosphere (Chanrion et al., 2017; Chou et al., 2018; Gordillo‐Vázquez et al., 2012; Pasko, 2008; Pasko et al., 2012; Riousset et al., 2010; van der Velde et al., 2007; Wescott et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…7.3), TLEs are a manifestation of the extraordinary impact of thunderstorms onto the Earth's atmosphere, and have as of yet unconstrained implications on atmospheric chemistry and the climate [977]. In particular, low altitude TLEs, together with in-cloud streamer coronas and their associated UV and near-UV flashes, may exert a greater role in atmospheric chemistry than previously thought [978].…”
Section: Transient Luminous Eventsmentioning
confidence: 99%
“…In this sense, Soler et al (2020) using observations from the Atmosphere-Space Interactions Monitor (ASIM) (Neubert et al, 2019), has associated strong sferics radio bursts to blue (337.0 nm) optical emissions from lightning. These emissions are assumed to be produced by streamer corona discharges in thunderclouds, whose nighttime climatology, global geographical and seasonal distributions have been recently published (Soler et al, 2021). Results from Soler et al, 2021 indicate that the northwest region of Colombia is the region of the world with most cloud corona discharges.…”
Section: Introductionmentioning
confidence: 99%
“…These emissions are assumed to be produced by streamer corona discharges in thunderclouds, whose nighttime climatology, global geographical and seasonal distributions have been recently published (Soler et al, 2021). Results from Soler et al, 2021 indicate that the northwest region of Colombia is the region of the world with most cloud corona discharges. Finally, it has been also suggested that fast streamer breakdown may be also related with the occurrence of TGF (Tilles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%